2009
DOI: 10.1111/j.1750-3841.2008.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Trans Fatty Acids in Ground Beef and Frankfurters due to Irradiation

Abstract: This study was conducted to investigate possible formation of trans fatty acids due to irradiation of ground beef and frankfurters. Ground beef and frankfurter samples were irradiated at doses of 0, 1, and 5 kGy at 4 degrees C, and stored at 4 degrees C for 7 d (ground beef) or 3 mo (frankfurters). After irradiation and storage of the samples, trans fatty acids along with other fatty acids were analyzed using a modification of AOAC method 996.01. The results showed that 1 kGy irradiation did not induce any cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similar results were previously observed [37,38]. Irradiating at 5 kGy decreased total amount of USFAs and increased the total amount of SFAs in beef lipids [39]. Another study reported that the decrease in USFAs during the irradiation process of oil is mainly due to a molecular structure moderate in fatty acids [40].…”
Section: Determination Of Fatty Acid Content In Irradiated and Non-irsupporting
confidence: 86%
“…Similar results were previously observed [37,38]. Irradiating at 5 kGy decreased total amount of USFAs and increased the total amount of SFAs in beef lipids [39]. Another study reported that the decrease in USFAs during the irradiation process of oil is mainly due to a molecular structure moderate in fatty acids [40].…”
Section: Determination Of Fatty Acid Content In Irradiated and Non-irsupporting
confidence: 86%
“…The maximum content of TFA was 0.8%, found in the oil extracted from perilla seed roasted at 180 °C for 75 min. Many studies have shown that TFAs can be formed in oil by such processes as deodorization, frying, irradiation, and partial hydrogenation (Mezouari and Eichner 2008; Fan and Kays 2009; Tsuzuki and others 2010; Dhaka and others 2011; Hou and others 2012). To our knowledge, there are few reports on the formation of TFAs in regard to the roasting of oilseed.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Lipids, including unsaturated fatty acids, are easily decomposed, saturated, and isomerized by gamma irradiation. [14,15] Radiation processing generates free radicals and hydrocarbon fragments and accelerates oxidation of unsaturated fatty acids that may induce some biochemical changes in food and influence its quality, such as the nutritional value. [16,17] Although irradiation has been found to be a useful process to increase the longevity of several agricultural products, but the effect of gamma irradiation and storage on the fatty acids of Syrian olive oils has not been investigated.…”
Section: Introductionmentioning
confidence: 99%